A MULTIMODAL DISCOURSE ANALYSIS (MDA) ON BIDADARI BERMATA BENING NOVEL BY HABIBURRAHMAN EL-SHIRAZY (ANALISIS WACANA MULTIMODAL DALAM NOVEL BIDADARI BERMATA BENING KARYA HABIBURRAHMAN EL-SHIRAZY) - Yanda, Diyan Permata; Ramadhanti, Dina (Jurnal Gramatika, 2018)
Multimodal discourse analysis is a new study in discourse studies to study text combined with images, colors, symbols, and other semiotic sources. The text and the semiotic resources areused to represent meaning. Therefore, a semiotic approach is used to study the implicit meaningof the text, images, and  olors used. In this study, a multimodal semiotics approach is used toexamine images, colors, and text on novel covers that reflect novel content. The images and col-ors were analyzed using Kress and Leeuwen's reading image theory, while the text as a reflec-tion of reality was analyzed using seven building task theory from James Paul Gee. This studyconcludes that in the use of colors, images, and texts contain a certain meaning that the readercan interpret in accordance with the reality presented in the text or narration.